13‐2: Novel Pixel Design In‐Plane Super‐Fast Response (ip‐SFR) LCD for Smartphone and PC Monitor. Issue 1 (29th May 2019) - Hanaoka, Kazutaka; Katayama, Takashi; Higashida, Shinpei; Kanashima, Atsuko; Sasaki, Takahiro; Yoshida, Hidefumi; Shimada, Shinji
Abstract : We developed a high‐speed response LCD for smartphones and PC monitors. By arranging the electrode pattern that is most efficient in obtaining high speeds in the pixel, high speed was realized while maintaining high transmittance. We prototyped a 5.3 inch drop‐in type VR specification high‐speed LCD display for smartphones, and good display characteristics were obtained.